Denture Services for Older Adults Within the Framework of Universal Health Coverage: A Scoping Review Using the who Universal Coverage Cube - Rika Meutia; Dharina Baharuddin; Meutia Zahara; Surna Lastri; Basri Aramico (Indonesian Journal of Global Health Research, 2026)
Older adults are particularly vulnerable to oral health problems, especially tooth loss, which affects chewing function, nutritional status, and quality of life. Dentures are an important rehabilitative intervention to address these issues. Although many countries, including Indonesia, have implemented Universal Health Coverage (UHC), coverage of denture services for older adults remains variable and limited. Objective isTo map denture services for older adults within the Universal Health Coverage framework using the WHO Universal Health Coverage Cube. Methods is This scoping review followed the Joanna Briggs Institute methodology and was reported in accordance with the PRISMA-ScR guidelines. Literature searches were conducted across multiple scientific databases and relevant grey literature sources. Eligible studies were analyzed descriptively and mapped according to the three dimensions of UHC: population coverage, service coverage, and financial protection. The results: A total of 20 studies were included in the review. The findings revealed considerable variation in denture services for older adults across countries. In terms of population coverage, older adults were not consistently prioritized as beneficiaries. Regarding service coverage, coverage was generally limited to basic removable dentures, with restrictions on materials and replacement frequency. In the financial protection dimension, older adults remained exposed to out-of-pocket payments despite formal inclusion of denture services in health policies. These findings indicate an imbalance across the three UHC dimensions. Conclusion is Although the UHC framework has been widely implemented, coverage of denture services for older adults remains suboptimal. Strengthening equity, service comprehensiveness, and financial protection is necessary to ensure more responsive health systems for ageing populations. The WHO Universal Health Coverage Cube provides a useful framework for identifying policy gaps.